A Study of acute toxicity to pyrethroid insecticide “KARATE” on fresh water alga Scenedesmus quadricauda (Turb.) Bereb. - Mohammed, Jasim; Mohammed, Jasim (University of Thi-Qar Journal of Science, 2010)
The study was conducted to evaluate the acute toxicity of insecticide (Karate) upon trough use green algae Scendesmus quadricauda as test organism in period time(24,72,96) hours under control conditions.The alga was growing in water giving from Al-Hilla river after filtering by Millipore filter paper (0.45)µm. Triplicates of samples where exposed to insecticides in a different concentrations (0.5,1,3)mg/l. Monitoring was proceeded every 24 hours for four days . This study include measure the optical density as indicators to density of algae and total count of cell number ,growth average and inhibition ratio was study ,also LT50 is calculated. Result show increase concentration of insecticide with increase concentration and recorded highinhibition ratio in concentration 3mg/l is (91.4%) after (96)h , and low value of LT50 in concentration (3)mg/l is (17.78). This study pointed out that insecticide differs in their toxicity according to concentration and time of exposure